2001
DOI: 10.1159/000050755
|View full text |Cite
|
Sign up to set email alerts
|

Executive Dysfunction in Spinocerebellar Ataxia Type 1

Abstract: Fourteen patients with spinocerebellar ataxia 1 (SCA1) and 11 controls with similar mean age and IQ estimates were submitted to a neuropsychological test battery comprising tests for IQ, attention, verbal and visuospatial memory as well as executive functions. Neuropsychological assessment yielded verbal memory and executive dysfunction while tests of visuospatial memory and attention were not significantly impaired in SCA1 as compared to controls. Test performance was neither related to the repeat length, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 23 publications
9
45
2
Order By: Relevance
“…In this study, we reveal visual memory deficits, impairments of verbal fluency, and executive dysfunction in SCA6 patients, which are similar to those described in patients with spinocerebellar ataxia type 1 [23], type 2 [24,25], and Machado-Joseph disease [26,27]. Cognitive dysfunction in these diseases is considered to be derived from the disruption of the cortico-cerebellar loop [23,24,26,27].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this study, we reveal visual memory deficits, impairments of verbal fluency, and executive dysfunction in SCA6 patients, which are similar to those described in patients with spinocerebellar ataxia type 1 [23], type 2 [24,25], and Machado-Joseph disease [26,27]. Cognitive dysfunction in these diseases is considered to be derived from the disruption of the cortico-cerebellar loop [23,24,26,27].…”
Section: Discussionsupporting
confidence: 80%
“…Cognitive dysfunction in these diseases is considered to be derived from the disruption of the cortico-cerebellar loop [23,24,26,27]. However, these diseases have extracerebellar involvement with degeneration of frontal lobes, thalamus, brainstem or basal ganglia, [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al [10] found that clinically, dementia was less frequent in SCA1 than in the other SCAs. The first comprehensive study of cognitive function in genetically confirmed SCA1 was described by Bürk et al [11]. They examined 14 patients with SCA1 using a neuropsychological test battery.…”
Section: Spinocerebellar Ataxia Typementioning
confidence: 99%
“…Frank dementia is occasionally observed, but more subtle cognitive abnormalities are probably common, if not universal. Executive dysfunction is especially notable [73,74] and may cause substantial impairment yet escape clinical attention during routine neurologic evaluations. Psychiatric disorders, including affective syndromes, personality change, and psychotic syndromes, may be present in as many as 80% of individuals with SCA [75••].…”
Section: Neuropsychiatric Manifestations Of Dominant Cerebellar Ataxiasmentioning
confidence: 99%